Socialization of Lupus Disease Awareness for Housewife Group of Genting Village, Ambarawa, Central Java - Stalis Norma Ethica; Ayu Rahmawati Sulistyaningtyas; Aditya Rahman Ernanto; Muhammad Ardi Afriansyah; Ana Hidayati Mukaromah (Universitas Mathla'ul Anwar Banten, 2020)
Lupus or Systemic Lupus Erythematosus (SLE) is a life-threatening chronic autoimmune disease with symptoms similar to those of other diseases. Frequent misdiagnosis of lupus increases the mortality rate of the disease. Public understanding is still low about Lupus, characterized by a variety of misperceptions about the disease, which still occurs. In rural area, Lupus is still often regarded as a virus transmitted and is associated with weak immune activity. There are still many women who do not yet know that they are a group that is more susceptible to Lupus than men. Various errors in people's perception of Lupus need to be corrected to increase public awareness of the disease. Efforts to correct misperceptions about Lupus have been done through Science and Technology for Community (Ilmu Pengetahuan dan Teknologi bagi Masyarakat, IbM) activities in counseling form to the housewife groups in Kalipucung Hamlet, Genting Village, Jambu District, Ambarawa, Central Java. Participatory approaches and tutorials have been carried out in the IbM activities through the provision of counseling materials, as well as the delivery of questionnaires before and after counseling. The results of the questionnaire analysis indicate that the counseling program could improve awareness about Lupus disease among community in rural area.